Influence of parameters of open-loop fiber optic gyro elements on measurement precision - Іванов, Сергій Вікторович (Eastern-European Journal of Enterprise Technologies, 2016)
The analysis of the output signal of the interferometric open-loop fiber optic gyro (FOG) is performed. It is based on the Jones matrix method taking into account the parasitic modulation (modulation is due to the photoelastic effect, causing connection of modes under transverse compression of the fiber), the polarizer extinction coefficient, rotation angles of the optical fiber axes relative to the polarizer axes. The influence of the FOG elements on measurement precision of angular velocity of the object is estimated. The proposed angular velocity measurement method is digital. The output signal intensity is measured in each modulation period at certain time points. Based on the measurement results, the phase shift of counter-propagating waves, which is proportional to the angular velocity of the object is computed. This method allows to exclude the synchronous detector and the LPF from the circuit, which simplifies the analog part of the circuit and reduces the influence of the errors made by the analog elements on the measurement precision. The FOG precision is greatly affected by the polarizer and the modulator. The FOG output signal has hardly-compensated polarization error. To reduce it, the polarizer with the extinction coefficient of at least 0.001 should be used. Particular attention should be paid to the improvement the modulator. Since the error caused by its imperfection is multiplicative by nature and may reach unacceptably high values. To reduce the measurement error, SLD with stable polarization and ellipticity parameters of radiation should be used.